Caminhos para a reforma psiquiátrica no Hospital Colônia Adauto Botelho (1980-2002) - Carvalho, Jakeline Santos (2018)
The current dissertation presents an analysis of the Psychiatric Reform process performed in the Colonia Adauto Botelho Hospital (HCAB) in Pinhais, part of the metropolitan region of Curitiba. The study comprehends the period between 1980 and 2000, which understands the moment that the first structural changes began in the institution, the deepening of those changes in the following decades, as well as both enactments of State Law of Psychiatric Reform in the state of Parana in 1995 and the Federal Psychiatric Reform Law of 2001. In this investigation we discussed the changes that occurred within the institution, and those that occurred on the legal arrangements, that is, the laws and ordinances on mental health in Brazil and in the Parana that guided the discussions of the antiasylum movement in the state of Parana. The research was performed from the perspective of the History of Madness and Psychiatry, which permitted to examine the sociocultural environment in which the institution was immersed, as well as to consider the several individuals that acted and keep acting in the institution and their practices. For such, as methodological resource, we used the discourse analysis, as to consider the statements in the sources, regarding the production of meanings and to the objective and subjective actions about madness and the psychiatric reform. With that, this dissertation was structured from three central axes: the presentation and discussion of the main laws and ordinances on mental health, created from the redemocratization movement of the country; the demonstration, based on the official documents of the institution, of the new projects developed and to whom they were directed to; and, finally, the discussion of various memories about the hospital and the Psychiatric Reform. Therefore, we highlight that the HCAB followed a similar path of other institutions in the country, since that the first internal reorganizations, at the beginning of the 1980, occurred without significant legal support at the time, but rather as a response to the precarious asylum conditions, which were frequent in psychiatric hospitals. This showed how the changes of the asylum model happened from the relation of horizontal powers, extended by extended by society and not as a single instance of power. Finally, the study allowed to assess the implications of madness in our society and the irregularities in the psychiatric reform and tin he HCAB in its incidences and limitations.